The many faces of populism current perspectives - Wejnert, Barbara; Woods, Dwayne (Bingley, U.K. : Emerald, 2014)
Populism comes in many guises. Both Berlusconis personalization of politics and the Northern Leagues anti-immigrant regionalist movement are viewed as examples of the phenomenon of populism. A type of left-wing populism embodied by Hugo Chavez swept across Latin America. Insurgent and anti-system movements and parties in places as different as the Netherlands, India, Norway, Thailand, Russia and the United States have experienced what have been labeled populists movements. Such varied manifestations beg the question: what is populism? The objective of this edited volume is to provide an answer by examining "the many faces of populism." The unifying element across the different explorations of the phenomenon of populism is that there is a shared genus that allows for a typology of the different faces of populism and a demarcation of what is not a form of populism.
The many faces of populism : diverse but not disparate / Dwayne Woods -- The many faces of populism in Italy : the northern league and Berlusconism / Dwayne Woods -- The post-modern populism in Italy : the case of the five star movement / Maria Elisabetta Lanzone -- Populism in Latin American politics / Carlos de la Torre -- Agrarian populism in Poland : peasants' political identity and mobilisation from democratisation to communism (1880-1989) / Frédéric Zalewski -- Iranian populism : its vicissitudes and political impact / Manochehr Dorraj -- Populism and democracy : not the same but interconnected / Barbara Wejnert -- Epilogue : finding populism today / Barbara Wejnert.
Print version record
Keywords: Political Science -- Political Ideologies -- General; Political ideologies; Political activism; Political structure & processes; Populism